2001
DOI: 10.3319/tao.2001.12.3.567(a)
|View full text |Cite
|
Sign up to set email alerts
|

ROCSAT-1 Satellite Observations of Magnetic Anomaly Density Structures During the Great Magnetic Storm of July 15-16, 2000

Abstract: Large scale ion density structures were observed by ROCSA T-1 at 630 km altitude over the South Atlantic anomaly (SAA) region during the great magnetic storm of July 15-16, 2000. The observed density structures were confined within 30° in longitude east of the SAA, and co-rotated with the SAA for over 8 hours. The magnetic anomaly density structures (MADS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…1. During this magnetic superstorm, ROCSAT-1 detected a large ion density depletion at low latitudes (o351S) in the nighttime ionosphere after magnetic storm activity reached its peak intensity, lasting 8 h through the end of the magnetic storm (Lin et al, 2001). The bottom panel of Fig.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…1. During this magnetic superstorm, ROCSAT-1 detected a large ion density depletion at low latitudes (o351S) in the nighttime ionosphere after magnetic storm activity reached its peak intensity, lasting 8 h through the end of the magnetic storm (Lin et al, 2001). The bottom panel of Fig.…”
Section: Introductionmentioning
confidence: 94%
“…Lin et al (2001) demonstrated that these large-scale density dropouts corotated with the South Atlantic anomaly (SAA) and were adjacent to regions of density enhancement, forming a magnetic anomaly density structure (MADS). While the large-scale density dropouts were detected in the southern hemisphere, ground-based global positioning satellite (GPS) total electron content (TEC) measurements have indicated large-scale storm-enhanced density (SED) in the northern hemisphere during magnetic superstorms (Foster et al, 2002;Kelley et al, 2004;Yin et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is interesting that similar observations of large density depletion events were again observed during the 6 -7 April 2000 and the 15 -16 July 2000 magnetic storms by ROCSAT-1 satellite, at 600 km altitude traversing the magnetic flux tube in the east-west direction. The 15 -16 July events were reported to correlate with the SAA region (Lin et al 2001). The large density dropout was further classified by Su et al (2002) in two groups of ESF plasma irregularities that occurred in either side of the midnight meridian during the storm recovery phase.…”
Section: Ionospheric Disturbance By Geomagnetic Stormmentioning
confidence: 99%